Clinical and Pathologic Features of Hispanic Endometrial Cancer Patients With Loss of Mismatch Repair Expression. Issue 6 (July 2016) - Kost, Edward R.; Valente, Philip T.; Lynch, Barnard A.; Krishnegowda, Naveen K.; Hertz, Alexandria M.; Hall, Kevin L.; Riddle, Nicole D.; Tekmal, Rajeshwar R.
Abstract : Objectives: Approximately 3% to 5% of endometrial cancers (EC) are associated with Lynch syndrome (LS). The clinical characteristics and prevalence of LS have not been well studied in the US Hispanic population. Hispanics are the largest and fastest growing ethnic minority group in the United States. We sought to characterize the demographics, tumor characteristics, and prevalence of loss of mismatch repair (MMR) protein expression in a large Hispanic population with EC. Methods: From January 1, 2005, to August 1, 2012, 83 women of Hispanic ethnicity diagnosed with EC 50 years and younger were identified. Clinical and pathologic data were abstracted from the electronic medical record. Tumor studies included immunohistochemistry of MLH1, MSH2, MSH6, and PMS2 and methylation of the MLH1 promoter. Results: Ninety-five percent of patients were overweight or obese. The mean body mass index was 40.1 kg/m 2, 75% had irregular menses, 36% had diabetes, 46% were nulliparous, and 95% had endometrioid histology. Thirteen patients (15.7%) had tumor MMR deficiency due to a presumed germline mutation (9 MSH6, 3 MSH2, and 1 MLH1). The pattern of MMR protein loss was consistent with the expected binding properties of the MMR heterodimer complexes. No significant difference was found in clinical or pathological variables between patients with and without MMR deficient tumors. Conclusions: The prevalence of molecular findings consistent with LS was at least as high as other populations of varied geography, race, and ethnicity. We found no reliable factors to include body mass index, family history, synchronous tumors, or pathologic tumor features to serve as triage markers for which ECs should be screened for MMR protein loss. Our findings support a recommendation for universal screening of ECs utilizing 2-antibody testing with MLH1 promoter methylation testing as indicated up to 60 years or older. Our recommendations should be generalizable to other Hispanic populations in the Southern United States.